A Review of Educational Programs to Reduce UTIs Among Individuals with SCI. Issue 5 (29th October 2013) - Mays, Rachel; McIntyre, Amanda; Mehta, Swati; Hill, Denise; Wolfe, Dalton; Teasell, Robert
Abstract Purpose To evaluate the effectiveness of educational programs in reducing urinary tract infections (UTIs) in individuals with spinal cord injuries (SCI). Methods A search of all relevant literature published up to and including July 2012 was conducted using multiple databases. Methodological quality was rated using the PEDro tool for randomized control trials (RCTs) and the Downs and Black tool for non‐RCTs; levels of evidence were assigned using a modified Sackett scale. Findings Four articles were selected for review. As a result of an education program, a level 2 prospective control trial reported a reduction in number of UTIs (p = .02), but a level 2 RCT did not. A pre–post study found a reduction in number of UTIs while a case–control study did not; however, these studies did not compute statistics. Conclusions There is limited positive evidence that education programs reduce the incidence of UTIs. Clinical relevance Optimal urinary health of individuals with SCI may be optimized via education programs that provide information and enhance skills.